Arbuscular Mycorrhizal Fungi Play More Important Roles in Saline–Sodic Soil than in Black Soil of the Paddy Field in Northeast China - Dongxue Jiang; Yuxin Yan; Jiaqi Li; Chenyu Zhang; Shaoqi Huangfu; Yang Sun; Chunyu Sun; Lihua Huang; Lei Tian (Agriculture)
Rice serves as the staple food for half of the world’s population. Given the expanding global population, the urgency to allocate land for rice cultivation is paramount. In Northeast China, saline–sodic and black soils represent two distinct soil types used in rice production. During rice growth, soil microorganisms, including arbuscular mycorrhizal fungi (AMF), play pivotal roles in nutrient uptake and resistance to biotic and abiotic stressors. While numerous studies have elucidated the role of AMF in enhancing rice growth and its adaptation to stress, the differences in AMF communities within paddy fields between different soil types have been largely overlooked. In this study, high-throughput sequencing technology was employed to analyze the diversity and community structure of AMF, and metagenomic sequencing was employed to analyze AMF functional gene differences between the two soil types (black and saline–sodic soils). At the same time, the commonalities and differences of the soil characteristics (nitrogen, phosphorus, potassium, pH, etc.) were verified in influencing AMF communities. The results indicated that Glomus was the predominant genus in both soil types, followed by Paraglomus. The overall abundance of AMF was higher at the heading stage than at the harvest stage, with Paraglomus showing greater adaptation to the saline–sodic soil environment. Total phosphorus (TP) was identified as the primary factor influencing AMF diversity at the heading stage. In the harvest stage, AMF community diversity was greater in saline–sodic paddy soil compared to black soil, a reversal from the heading stage. Further analysis of the functional genes of Rhizophagus intraradices revealed that gene activity in the heading stage of saline soils significantly surpassed that in black soils, suggesting that R. intraradices plays a more crucial role in saline environments. Additionally, spore density and the content of easily extractable glomalin-related soil protein were relatively higher in saline–sodic soil than in black soil. Thus, it may be inferred that AMFs are more vital in saline–sodic soils than in black soils of the paddy fields in Northeast China. This study may offer valuable insights into the utilization of AMF in paddy fields in Northeast China.